Gender Goals: Defining Masculinity and Navigating Peer Pressure to Engage in Sexual Activity. Issue 5 (October 2019) - Duckworth, Kiera D.; Trautner, Mary Nell
A significant part of hegemonic masculinity is proving one's heterosexuality though sexual experiences. Peer pressure to conform is particularly acute for adolescent boys and young men. We analyze interviews with 87 boys in middle school, high school, and college about how their masculinity goals and subsequent achievement of those goals influence their navigation of pressure to engage in sexual relations with girls and women to "prove" themselves. Our findings show that, while boys and young men recognize dominant notions of hegemonic masculinity, most do not subscribe to those uncritically. Rather, they struggle to balance personal ideas about masculinity with consistent pressure from others to demonstrate their heterosexuality. As a result, they employ various strategies to negotiate such pressures, including avoidance, acceptance, and outright rejection of this particular expectation. These strategies, however, ultimately contribute to a broader gender culture among adolescents in which expectations and privileges associated with hegemonic masculinity that dominate U.S. culture remain largely unchallenged.